Performance of Coir Fiber Addition for Clay as a Sub-Grade for Pavement Design - R. P., Munirwan; M., Munirwansyah; ., Marwan; Putra Jaya, Ramadhansyah; V., Kamchoom (IOP Publishing, 2020)
Clay soil behavior often becomes problematic with building construction, it is about the shrink-swell behavior in clay when influenced by water content. Coconut husk fiber (coir fiber), in general, is an industrial waste which is still infrequent to be re-used. This study aims are to determine the effect of coir fiber addition for mechanical stabilization of clay soil in terms of CBR (California Bearing Ratio) value. Soil samples used for laboratory tests were collected from Ulee Glee area of Pidie Jaya Regency. According to AASHTO classification, the soil category is A-7-5 (25) while for USCS classification, the soil is OH (Organic High). The percentage of added coir fiber was 0%, 0.2%, 0.4% and 0.6% of the dry weight of the soil with a coir fiber length of 2 and 3 cm. Two treatments of clay-coir fiber mixing method were applied namely direct mixing and mixing by layers. The results of natural soil compaction test obtained that OMC (Optimum Moisture Content) value and dry soil weight (γdmax) was 26.8% and 1.34 gr/cm3 respectively. The highest CBR results were obtained for clay soil with 0.4% coir fiber 3 cm (direct mix) with CBR value = 17.7%. Furthermore, the lowest CBR value is 10% for percentage of 0.2% with coir fiber length 2 cm (by layer). In general, high organic clay soil with coir fiber mixture addition is able to increase the CBR values if compared to CBR of natural soil which is 8.15%. Thus, the use of coir fiber in this study is able to improve soil bearing capacity which is useful for construction material in the site.